COMBINED NEAR-INFRARED AND X-RAY DIFFRACTION INVESTIGATION OF THE OCTAHEDRAL SHEET COMPOSITION OF PALYGORSKITE - Gionis V.; Chryssikos G.D.; Kacandes G.H.; Kastritis I.D. (My University, 2007)
The octahedral composition of palygorskite in more than 300 samples from the Pefkaki deposit, W. Macedonia, Greece, has been studied by near-infrared (NIR) and X-ray diffraction (XRD), and evaluated according to the formula yMg5Si8O20 (OH)2·xMg2Fe2III Si8O20(OH)2·(1-x-y) Mg2Al2Si8O20 (OH)2. Included in the study were PFI-1 and several commercial palygorskites. Our analysis of 2nd derivative NIR spectra shows that the dioctahedral composition is adequately described by three sharp overtone bands representing AlAlOH, AlFeIIIOH and FeIIIFeIIIOH in M2 dioctahedral sites, and that the summed intensity of these bands is proportional to the amount of dioctahedral component present (1-y). The samples show large variations in the degree of dioctahedral FeIII-for-Al substitution with FeIII occupying up to 70% of the dioctahedral M2 sites. Ternary analysis shows that the distribution of dioctahedral Al and FeIII is not random, but displays a tendency towards homoionic pairing. An overtone band at 7214 cm-1 and several combination bands are indicative of a trioctahedral Mg3OH component (y), and their appearance correlates with a distinct palygorskite signature in thermogravimetric analysis. Nevertheless, these bands cannot be used reliably for the quantification of a trioctahedral palygorskite component due to their close similarity to those of sepiolite. To circumvent this problem, we have evaluated y indirectly by calculating the difference between 1-y and the total concentration of palygorskite determined by the normalized intensity of the d110 XRD peak of palygorskite at 10.4 Å. Using this methodology, we have found that the samples conform to a trioctahedral limit of y ≈ 0.55, although within this limit they display large variations in octahedral character. Finally, we extend the above methodology to PLS chemometrics and show how NIR can be used to determine palygorskite content routinely in multimineralic geological samples. Copyright © 2007, The Clay Minerals Society.
Keywords: GREECE; NEAR-INFRARED SPECTROSCOPY; OCTAHEDRAL COMPOSITION; PALYGORSKITE; X-RAY DIFFRACTION